Differences in head impact exposures between youth tackle and flag football games and practices: Potential *implications for prevention strategies - Sarmiento, K.; Waltzman, D.; Devine, O.; Zhang, X.; DePadilla, L.; Kresnow, M.-J.; Borradaile, K.; Hurwitz, A.; Jones, D.; Goyal, R.; Breiding, M. J. (The American Journal of Sports Medicine, 2021)
Background: Interventions designed to reduce the risk for head impacts and concussion in youth football have increased over the past decade; however, understanding of the role of regular game play on head impact exposure among youth tackle and flag football athletes is currently limited.